Unraveling participant motivation dynamics in local-centric secondhand digital sharing platforms - Hana Kim; Gyuhwan Kim; Taehwa Lee; Joohee Lee (PLoS ONE, 2025)
This study investigates the motivational and attitudinal drivers of user engagement in local-centric digital sharing platforms (LDSPs), with a focus on secondhand consumption through Karrot Market in South Korea. Grounded in Self-Determination Theory and the Theory of Reasoned Action, we examine how economic, environmental, interaction, and reputation motivations, together with attitudes and socioeconomic characteristics, influence individuals’ behavioral intentions to purchase secondhand goods. Using structural equation modeling (SEM) on survey data from 449 Seoul residents with prior Karrot use experience, we found that economic motivations were the strongest direct predictor of both attitudes (i.e., positive stance toward buying secondhand on Karrot) and behavioral intentions (i.e., intention to buy secondhand on Karrot). Reputation motivation also exhibited a direct effect on behavioral intention, while environmental and interaction motivations showed influences on behavior only indirectly through attitudes. Multigroup SEM further revealed that these pathways vary by age and marital status, indicating heterogeneous motivational patterns across user segments. Environmental motivation was more salient among users in their 20s and 50s, while reputation held greater importance for older users. Our findings highlight the central role of attitudes as mediators in translating relatively more intrinsic motivations, particularly for environmental and social drivers, into behaviors. Taken together, we offer practical insights for platform design and policy interventions, including strategies to visualize environmental impact, incentivize sustainable behaviors, and tailor engagement approaches by user characteristics. By decoding the multidimensional motivations behind LDSP participation, this research contributes to emerging scholarship on local-centric secondhand commerce and informs efforts to advance community-based circular consumption.